(untitled) (AmS-Skrifter, 2026)
Oval brooches are considered one of the most diagnostic elements of female Viking costume, and they frequently are used to indicate that Scandinavian women accompanied their seafaring menfolk when settling new lands. But while they were known in virtually every other area of Scandinavian settlement in the British Isles, they were missing entirely in the Isle of Man, which presumably was conquered and settled by Hiberno-Vikings after about 870. Their conspicuous absence – and general lack of securely sexed female burials among the Viking graves in Man – gave rise to the assumption that those settlers were all-male groups of warriors, who subsequently married local Christian women, and this formed the basis for far-reaching conclusions regarding the early Viking-Age in the Island. This long-lived notion has been challenged in 2015, but in December 2018, the discovery of two oval brooches in the Isle of Man confirmed the doubts about the previous conclusions regarding the nature of interethnic social contact on the late-ninth-century Man. This paper presents the currently unpublished Manx oval brooches, reconstructs the now-obsolete former interpretations and the objections to them, and discusses the impact of this single new discovery on the scholarly perception of early-Viking-Age Manx history.